Formation Mechanism of Preferential Flow Paths and Seepage Characteristics of a Novel Growable Pile for Heap Leaching of Rare Earth - Wei Ju; Jianhua Yang; Zemin Wang; Chi Yao; Xiaobo Zhang (Advances in Materials Science and Engineering)
In the traditional heap leaching of rare earth minerals, the top of the rare earth pile is covered with leaching liquid. This creates trouble for vegetation restoration carried out timely on the top of the pile. In order to solve this trouble, a novel pile structure into which leaching liquid is laterally injected is proposed for heap leaching of rare earth. In this study, a laboratory test is carried out to study the formation and distribution of preferential ﬂow paths for the rare earth pile under a horizontal liquid injection condition. Furthermore, numerical simulations based on a dual-permeability model are conducted to investigate the influence of the preferential ﬂow paths on the seepage characteristics in the rare earth pile. The results show that, under the horizontal liquid injection condition, the fine particles of the rare earth move away from the liquid injection end and also toward the lower part of the pile. The migration of the fine particles results in the formation and connection of macropore, thereby generating preferential ﬂow paths in the rare earth pile. The preferential ﬂow paths are mainly distributed in the lower part of the pile near the liquid injection end. This causes the fluid in the lower part of the pile to seep faster significantly than that in the upper part. Within the region where the preferential ﬂow paths develop, the seepage in the early stage of the horizontal liquid injection is dominated by preferential ﬂow. The preferential ﬂow is more significant at the locations farther away from the liquid injection end.